Sex Moderates the Relationship That Number of Professional Fights Has With Cognition and Brain Volumes - Bennett, Lauren L.; Stephen, Steve J.; Bernick, Charles; Shan, Guogen; Banks, Sarah J. (Frontiers in Neurology, 2020)
Objective: Incidence of concussions and report of symptoms are greater amongst women across sports. While structural brain changes and cognitive declines are associated with repetitive head impact (RHI), the role of sex is not well understood. This study aimed to determine if there is a moderating effect of sex on the relationship number of professional fights has with cognitive functioning and regional brain volumes in a cohort of boxers, mixed martial artists, and martial artists. Methods: 55 women were matched with 55 men based on age, years of education, ethnicity, and fighting style. Cognition was assessed via CNS Vital Signs computerized cognitive battery and supplemental measures. Structural brain scans, demographic data, and number of professional fights (NoPF) were also considered. Matched pairs were compared via analysis of covariance, accounting for total brain volume. Within-subject moderation models were utilized to assess the moderating effect of sex on the relationship between NoPF and brain volumes and cognitive performance. Results: Men were observed to have poorer performance on measures of psychomotor speed when compared to women. On a series of analyses assessing the role of sex as a moderator of the relationship between NoPF and regional brain volumes/cognitive performance, a significant moderation effect was observed across multiple measures of cognitive functioning, such that men had poorer performance. Differences in numerous regional brain volumes were also observed, such that the relationship between NoPF and brain volumes was steeper amongst men. Conclusion: Sex was observed to be an important moderator in the relationship between NoPF, aspects of cognitive functioning, and volumes of numerous brain regions, suggesting that sex differences in neuroanatomic and cognitive response to RHI deserve further attention.